Effects of silane treatment on salivary protein contamination during the bonding of lithium disilicate ceramic. Issue 17 (1st September 2020) - Kim, Hyun-Jung; Kim, Sehoon; You, Seung-Hyun; Cho, Sung-Geun; Choi, Kyoung-Kyu; Kim, Duck-Su
Abstract: In this study, the effect of saliva contamination and cleaning procedures on the bond strength of lithium disilicate (LS2) ceramics was investigated at different timings of silane treatment. Micro-tensile bond strength (μTBS) test using a universal testing machine was performed ( n  = 24). For analysis of adhesive surface characteristics, water contact angle was measured ( n  = 3). After saliva contamination, the salivary protein level using the Bradford assay was quantified ( n  = 3). The pre-conditioned surfaces were observed using a field emission-scanning electron microscope (FE-SEM). Saliva contamination and the silane treatment timing significantly affected the μTBS of LS2 ceramics ( p  < 0.05). However, cleaning methods did not show any significant differences in μTBS ( p  > 0.05). Water contact angle increased after silane treatment. High concentration of salivary protein was detected in the group where saliva contamination occurred before silane treatment ( p <  0.05). FE-SEM analysis showed that the etched surfaces of the contaminated LS2 specimens were covered with oral bacteria and other salivary components. It also showed that ultrasonic cleaning was effective in eliminating salivary contaminants while air-water spray was not. Saliva contamination of the surface of LS2 ceramics deteriorates μTBS. To minimize the effect of saliva contamination, prompt silane treatment to etched surface of LS2 ceramic is recommended.